1995
DOI: 10.1111/j.1399-6576.1995.tb04203.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes due to Trendelenburg positioning and pneumoperitoneum during laparoscopic hysterectomy

Abstract: More prolonged gynecological laparoscopic operations are being performed in recent years, and a steeper head-down position is required. The early reports of hemodynamic changes during gynecologic laparoscopy are conflicting, and the effects of anesthesia, head-down tilt and pneumoperitoneum have not been clearly separated. Invasive hemodynamic monitoring was carried out in 20 female ASA Class I-II patients who underwent laparoscopic hysterectomy. Baseline measurements were made in the supine, supine-lithotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(93 citation statements)
references
References 23 publications
5
80
0
8
Order By: Relevance
“…Russo et al demonstrated that headdown positioning was capable of increasing the venous return, enlarging left ventricular end-diastolic volume, and elevating the SV in normal and elevated IAP (21). Hirvonen et al demonstrated that the Trendelenburg position in awake and anesthetized patients increased pulmonary arterial pressures, CVP and pulmonary capillary wedge pressures, and these pressures further increased at the beginning of IAH (22). The elevated IAP influences the intrathoracic pressure by pushing the diaphragm upward, thus decreasing respiratory system compliance (23).…”
Section: Discussionmentioning
confidence: 99%
“…Russo et al demonstrated that headdown positioning was capable of increasing the venous return, enlarging left ventricular end-diastolic volume, and elevating the SV in normal and elevated IAP (21). Hirvonen et al demonstrated that the Trendelenburg position in awake and anesthetized patients increased pulmonary arterial pressures, CVP and pulmonary capillary wedge pressures, and these pressures further increased at the beginning of IAH (22). The elevated IAP influences the intrathoracic pressure by pushing the diaphragm upward, thus decreasing respiratory system compliance (23).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da PCV ter sido estudada comparativamente na presença de doenças pulmonares, não foi encontrado estudo comparativo sobre o uso da PCV e da VCV em anestesia com o uso de pneumoperitônio, onde a complacência e a resistên-cia pulmonares sofrem alterações, mesmo que reversíveis ao fim do procedimento cirúrgico. Diversos estudos demonstraram que a freqüência cardíaca não sofre alterações significativas durante o pneumoperitô-nio [32][33][34][35][36][37][38][39][40][41] . O aumento da freqüência cardíaca foi similar nos dois grupos, após a aplicação do PPC, sem diferenças entre a ventilação com o controle do volume ou o controle da pressão.…”
Section: Resultsunclassified
“…Although PCV has been comparatively studied in the presence of pulmonary diseases, no comparative study was found on PCV and VCV in anesthesia with pneumoperitoneum, where pulmonary compliance and resistance are changed, even if reversible at the end of surgery. Several studies have shown that heart rate is not significantly changed during pneumoperitoneum [32][33][34][35][36][37][38][39][40][41] . Heart rate increase was similar for both groups after CPP without differences between volume controlled or pressure controlled ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Bugüne kadar yapılan çalışmalarda, derin trendelenburg pozisyonu ve karbondioksit (CO 2 ) insüflasyonunun KAH ve ortalama arter basıncında (OAB) artış yaptığı bildirilmiştir (13). Kolesistektomi ve histerektominin tersine, laparoskopik kolon cerrahisi uzun anestezi ve cerrahi süresi gerektirmektedir (14).…”
Section: Discussionunclassified